Performance of Bleach Method Sputum Smear Microscopy for the Diagnosis of Tuberculosis in a Highly Endemic District in Lima, Peru - Rosales-Rimache, Jaime (2022)
Background: Sputum smear microscopy (SSM) is a screening test used to diagnose tuberculosis (TB); however, its performance and sensitivity are relatively low, which can lead to false negatives. We designed a cross-sectional study to estimate the performance of SSM that includes a pretreatment based on sputum digestion with bleach (sodium hypochlorite) for the diagnosis of TB. Methods: We evaluated 73 sputum samples from patients with a diagnosis of TB confirmed by the Xpert MTB/RIF test and 114 samples from patients without TB. We performed sputum digestion using a 5% sodium hypochlorite solution, centrifuged at 2000 rpm for 15 min. We prepared smears for direct and bleach-treated SSM and used Ziehl–Neelsen staining. Results: The bleach-treated SSM obtained absolute identification of the cases of TB confirmed by the Xpert test, compared to 95.9% identified by the direct smear method (without bleach treatment). We also found a significant increase (p < 0.001) in the recovery of acid-fast bacilli (AFB) obtained by the bleach-treated SSM (293.8 ± 215.1 AFB) compared to the direct SSM method (222.9 ± 195.5 AFB). The AUC of the bleach-treated SSM and direct SSM was 100% and 96.6%, respectively. Conclusion: The bleach-treated SSM performs better than the direct SSM in identifying AFB and increasing the bacillary count in the sputum samples.